Beyond race: Recruitment of diverse participants in clinical genomics research for rare disease - Young, Jennifer L.; Halley, Meghan C.; Anguiano, Beatriz; Fernandez, Liliana; Bernstein, Jonathan A.; Wheeler, Matthew T.; Tabor, Holly K.; , Undiagnosed Diseases Network Consortium (Frontiers in Genetics, 2022)
Purpose: Despite recent attention to increasing diversity in clinical genomics research, researchers still struggle to recruit participants from varied sociodemographic backgrounds. We examined the experiences of parents from diverse backgrounds with enrolling their children in clinical genomics research on rare diseases. We explored barriers and facilitators parents encountered and possible impacts of sociodemographic factors on their access to research. Methods: We utilized semi-structured interviews with parents of children participating in the Undiagnosed Diseases Network. Interview data were analyzed using comparative content analysis. Results: We interviewed 13 Hispanic, 11 non-Hispanic White, 5 Asian, and 2 biracial parents. Participants discussed different pathways to clinical genomics research for rare disease as well as how sociodemographic factors shaped families’ access. Themes focused on variation in: 1) reliance on providers to access research; 2) cultural norms around health communication; 3) the role of social capital in streamlining access; and 4) the importance of language-concordant research engagement. Conclusion: Our findings suggest that variables beyond race/ethnicity may influence access in clinical genomics research. Future efforts to diversify research participation should consider utilizing varied recruitment strategies to reach participants with diverse sociodemographic characteristics.